Between Great Transformation and Politics as Usual: Formal and Informal Security Governance in EU Counterterrorism Policy - Hendrik Hegemann (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Debates about EU counterterrorism policy commonly oscillate between promises of a supranational 'great transformation' and reminders regarding the realities of intergovernmental 'politics as usual'. Yet, the paper argues that post-9/11 EU counterterrorism has come to encompass a broader set of formal and informal policies and structures that extends beyond this dichotomy. The emerging system of security governance aims to reconcile a common interest in cooperation and coordination with member states' reluctance to delegate substantial competences and resources. The paper draws on the security governance concept to grasp the ensuing complexity and offer a broader conceptual basis for the analysis EU counterterrorism cooperation. First, it identifies four key dimensions of security governance based on the existing literature. Second, it maps EU counterterrorism cooperation along these four dimensions, points to the variation of formal and informal security governance, and identifies some overall trends. Third, it identifies three main dynamics driving the emergence of formal and informal security governance by lining out a power-based, a functional, and a knowledge-based perspective.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330